Therapeutic effects of chewable fluralaner against Sarcoptes scabiei infestations in dogs - Khushboo, Richa; Singh, Shanker K; Kumari, Sanju; Gulmire, Suraj K; Jaiswal, Amit; Srivastava, Mukesh; Kumar, Gulshan (Indian Journal of Veterinary Medicine, 2024)
Scabies, also known as sarcoptic mange, is a potentially contagious ectoparasitic disease that poses a threat to both human and animal health. The majority of conventional medications that are suggested for the treatment of sarcoptic mange require repeated administration over a period of several weeks and are regarded as harmful to both pets and pet owners. A recently developed long-acting oral ectoparasiticide of the isoxazoline class is called fluralaner. Therefore, the current study’s objective was to assess the therapeutic effects of a single dose of chewable fluralaner against canine sarcoptic mange. Nine dogs were enrolled who tested positive for Sarcoptes scabiei mite infestation and had a pinnal-pedal scratch reflex. The diseased dogs were given a single oral dose of fluralaner chewable at a rate of 25-56 mg/kg body weight. Six more healthy dogs were enrolled as healthy controls. Blood samples were collected from each diseased dog prior to the start of therapy and on day 21 post-therapy, and were used to analyse the haemato-biochemical changes. The haemato-biochemical panels of dogs with sarcoptic mange differed significantly from those of healthy dogs. None of the treated dogs had any S. scabiei mites on day 21 post-therapy. On day 21 post-therapy, it was found that the sarcoptes-induced skin lesions (SSLS) in dogs treated with fluralaner had improved by a total of 83.6 percent. Except for alanine aminotransferase (ALT), all altered haemato-biochemical panels of ill dogs returned to normalcy on day 21 following therapy. Fluralaner was found to be effective and safe enough to treat canine sarcoptic mange with a single oral dose. To corroborate the results of this study, additional research involving a large number of dogs with sarcoptic mange is required.